Contemporary Thai Horror: The Horrific Incarnation of Shutter - Ainslie, Mary (Asian Cinema, 2011)
This article explores the creation, discourses, and distribution of the 2004 New Thai horror film Shutter. A high-grossing film nationally and internationally, Shutter is based in Bangkok and follows a story of supernatural revenge by the spirit of a young upcountry woman who returns to wreak vengeance upon the men and former boyfriend who abused her in life. While considered by Bangkok fans to be the “best” Thai horror ever and “the only genuinely scary Thai movie,” this paper will argue that Shutter ironically signalled a deliberate departure from traditional Thai horror aesthetics and narrative structure. Instead, shaped in favor of a pan-Asian “look” and appeal and one familiar to non-Thai viewers (through films such as Ringu, etc.), it thereby paradoxically achieved success as a “Thai film” while erasing many cultural specificities of Thai cinema. Significantly, its 2008 Hollywood remake was set in Japan starring American actors. This paper explores the ramifications of such redesigning to both the Thainess of Shutter’s subject matter and its wider social implications.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9hYy4yMi4xLjQ1XzE